ASUHAN KEPERAWATAN PADA IBU HAMIL NY.B G1P0A0 (24 MINGGU) DENGAN LOW BACK PAIN DI CIMAHPAR KECAMATAN BOGOR UTARA KOTA BOGOR - Mutya Ayu Septia (2022)
Background: Pregnancy in the second trimester is often painful. This pain causes fear and anxiety so that it can increase stress and drastic physiological changes during pregnancy in the second trimester. Pain on the back of pregnant women is one of the most frequently reported complaints among pregnant women in the second trimester. Low Back  Pain tends to occur in the second trimester of pregnancy because it is pain that occurs due to changes in posture that occur due to an increase in the weight of the uterus which causes an increase in the angle of spinal curvature. An increase in the angle of curvature causes flexibility and mobility and the lumbar spine to decrease. Method: This study uses a case study method.  nursing care for pregnant women Mrs.  B (GIPOA0) in the second trimester of pregnancy in Cimahpar, North Bogor District, Bogor City, 21 years old and pregnant in the second trimester of pregnancy which was carried out by collecting data through home visits, interviews, observations, physical examinations and collection of Tuinnyt data such as laboratory results. Results: Diagnosis  the main nursing care is acute pain associated with physiological agents (musculoikeletal) Pain measurement using the intensity of the mumeric nerves 0 10. After administering vital signs Implementation of nursing actions according to priorities that have been made and completed, the next diagnostic intervention Within 3x24 hours of acute venereal problems related to physiological agents  (Musculoskeletal) can be overcome. Conclusion: do yoga exercises to treat low back pain. Keywords : Pregnancy, Low Back Pain, Nursing Care